Ocular manifestations of rheumatic diseases - Kemeny-Beke, Adam; Szodoray, Peter (International ophthalmology, 2020)
Purpose Our aim was to summarize key aspects of the pathomechanism and the ocular involvements of rheumatic and systemic autoimmune diseases. Methods Apart from a paper in French (Morax V, Ann Oculist 109:368–370, 1893), all papers referred to in this article were published in English. All the materials were peer-reviewed full-text papers, letters, reviews, or book chapters obtained through a literature search of the PubMed database using the keywords ocular manifestations; pathogenesis; systemic inflammatory rheumatic diseases; rheumatoid arthritis; osteoarthritis; fibromyalgia; systemic lupus erythematosus; seronegative spondyloarthritis; ankylosing spondylitis; reactive arthritis; enteropathic arthritis; psoriatic arthritis; systemic sclerosis; polymyalgia rheumatica and covering all years available. Some statements articulated in this paper reflect the clinical experience of the authors in their tertiary-referral center. Results Ophthalmic disorders are categorized by anatomical subgroups in all rheumatic diseases. The most common ocular manifestations are diverse types of inflammations of different tissues and dry eye disease (DED). Conclusion The eye could be a responsive marker for the onset or aggravation of an immune reactivation in many rheumatic diseases, furthermore, ocular findings can antedate the diagnosis of the underlying rheumatic disease. By recognizing ocular manifestations of systemic rheumatic diseases it might be possible to avoid or at least delay many long term sequelae.